Biolegality, the Forensic Imaginary and Criminal Investigation - Machado, Helena (2013)
This text discusses some aspects of the local configurations of social representations and uses of DNA technology in criminal investigations in Portugal. The approach to the sociotechnical network which aligns forensic science with state governance policies, criminal investigation practices and laws, and the cultural imaginaries surrounding DNA and criminal investigation work is based on the concepts of biolegality and the forensic imaginary, which are, in turn, anchored in notions of biocitizenship and bioidentification, respectively. An interpretative and qualitative theoretical-methodological perspective has been adopted, based on an analysis of legislation and an understanding of the meanings and relevance attributed to the use of DNA technology by members of the Portuguese Criminal Police. The objective is to discuss aspects of the local tensions created by processes involving the export of DNA technology, which has its origins in societies and cultures with different traditions of technology governance, regulation of criminal investigation procedures and submission of evidence in court.